ChemInform Abstract: Water at Interfaces. Issue 36 (August 2016) - Bjoerneholm, Olle; Hansen, Martin H.; Hodgson, Andrew; Liu, Li‐Min; Limmer, David T.; Michaelides, Angelos; Pedevilla, Philipp; Rossmeisl, Jan; Shen, Huaze; Tocci, Gabriele; et al.
Abstract: Review: 306 refs.